A profissionalidade e a socialização entre docentes na escola: relatos de professoras - Ana Beatriz Siqueira Moraes (2021)
This study was developed in the Professional Master's Program in Education and Teaching, at the Faculty of Education at UFMG, in the line of research on Didactics and Teaching: Teaching, Assessment and Professionality. It was carried out from the perspective of qualitative research and based on the methodology of narrative research. It aimed to understand how a group of teachers perceive the relationship between the construction of teaching professionality and socialization situations, formal and informal, with their peers at school, throughout their trajectories. The research had the participation of a group composed of nine teachers, who taught in a state school in the city of Belo Horizonte in the final years of elementary school. The study of the concept of teaching professionality was supported, among others, by Ramalho, Núñez and Gauthier (2004), who understand that teaching professionality refers to the knowledge, skills and attitudes of professional action. The concept of teacher socialization was based on Lacey (1977), who addresses socialization as the development of behaviors and perspectives as the individual is confronted with different social situations. Socialization in its relationship with teaching knowledge was studied as outlined by Tardif (2014) and Nóvoa (2017), in particular, respectively, the approach to the social provenance of teaching knowledge and the concept of position. The foundation of narrative research methodology took place in dialogue with Clandinin and Connelly (2015) and Suárez (2017b). The field research instrument was inspired by the theoreticalmethodological perspective of Suárez's "Narrative Documentation of Pedagogical Experiences" (2017b). For the treatment of narrative data, we followed Clandinin and Connelly (2015) and thus, we dedicated ourselves to carrying out the transition from “field texts” to “research texts”, also using the “interweaving approach” proposed by them. The conclusions indicate that teachers understand that socialization situations are powerful for the construction of teaching professionality, but that in the educational routine, in the formal sphere, there are obstacles to this achievement. As part of the dissertation, an Educational Resource was created. The Resource is a proposal for the development of a project, whose core is the preparation, by teachers, of a notebook to record their school stories. This research is justified because it aims to contribute to perceptions about teaching professionality and, more specifically, because it values teaching knowledge and the possibilities of learning among peers.